The Model Media Audiovisual Sebagai Media Pembelajaran BIPA Untuk Mengenalkan Kosakata Bahasa Batak Pakpak Melalui Cerita Rakyat - Nissa, Khairunissa; Ginting, Pivi Turbana Br; Wibowo, Setiyo; Syahfitri, Dian (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2025)
This research aims to develop and analyze the use of audiovisual media as a medium for learning Indonesian for Foreign Speakers (BIPA) in introducing Batak Pakpak language vocabulary through the folklore "The Origin of Rice Pulut". Audiovisual media was chosen because of its ability to present information in a more interesting and interactive way, which can make it easier for students to understand new things. The folklore "The Origin of Rice Pulut" is used as the main material because it has cultural and linguistic richness that can be used as a context to introduce a contextual understanding of the Batak Pakpak language. This research uses literature study as the main research method to collect, analyze and formulate theories and findings relevant to the topic "Audiovisual Media Model as a BIPA Learning Media to Introduce Batak Pakpak Language Vocabulary Through Origin Folklore Ushul Padi Pulut'". In this literature study, the author reviews various sources such as books, journals, articles, research reports, and online sources related to language learning, especially Indonesian for Foreign Speakers (BIPA), the use of audiovisual media in education, and the application of folklore as a means of language and culture learning. The results of the research show that the audiovisual media developed can help BIPA learners understand the Batak Pakpak language in a more enjoyable and effective way. Using folklore as context also increases cultural understanding while enriching learner understanding. It is hoped that this media can be used as a reference in learning regional languages ​​for foreign speakers learning Indonesian.